Aijuvi 1.0: A Didactic Model Proposal for Teaching Finance Using Video Games - Flores Jaime, Jesús Gilberto; Velázquez Sagahón, Francisco Javier; Vázquez García, Juan Iván (CIENCIA ergo-sum; Vol. 32 (2025): CIENCIA ergo-sum, 2025)
A well-crafted didactic model is crucial to optimize learning outcomes by seamlessly integrating content with innovative pedagogical strategies. This research aims to propose a cutting-edge didactic model that employs video games to teach personal finances in English. The Aijuvi 1.0 model, rooted in the theory of Design-Based Research, bolstered by Constructivism, was designed, and a tool was employed to gauge student motivation. The findings, in this case, reveal that video games can be used effectively to teach Personal Finance in English.